Advertising Effectiveness for Recruitment and Retention in a Trial of Yoga for Smoking Cessation. Issue 4 (4th July 2022) - Dunsiger, Shira I.; Bock, Beth C.; Horowitz, Santina; Lantini, Ryan; Jennings, Ernestine; Thind, Herpreet
ABSTRACT: Background: Few cessation studies have examined their recruitment methods to determine the most effective methods for enrollment and retention. Purpose: Data from a randomized controlled trial of yoga for smoking cessation was used to evaluate recruitment methods (e.g., radio, referral) and their relationship to enrollment, participant characteristics, and retention at end of treatment (EOT). Methods: Screening data from 1065 adults were analyzed for recruitment method, eligibility, randomization, and retention through EOT using Analysis of Variance and Chi-squared tests. Costs per enrolled participant were calculated. Results: Rates of participant accrual from screening through randomization differed by recruitment method (p < .05), although there were no differences in retention post-randomization. Among randomized participants, the majority were recruited via radio (44%) and the least number via newspaper (5%). There were differences in baseline psychosocial (i.e., nicotine dependence, readiness to quit) and demographic (i.e., age, employment) characteristics of randomized participants (n = 227, 55.5% women) across recruitment methods. Differences in costs between recruitment methods (p < .001) were noted. Discussion: Recruitment methods differed substantially in their cost and ability to attract individuals who would ultimately enroll. Translation to Health Education Practice : This investigation highlights the need to combine different recruitment methods to attract diverse individuals into cessation treatments. A AJHE Self-Study quiz is online for this article via the SHAPE America Online Institute (SAOI) http://portal.shapeamerica.org/trn-Webinars